An exploration of osteopaths' views and experiences regarding the identification of, and provision of advice for, urinary incontinence in women: A qualitative study using framework analysis. (June 2018) - Robinson, Maria; Ford, Sarah L.; Goodman, Linda B.
Abstract: Background: Urinary incontinence (UI) may be defined as a storage symptom of the lower urinary tract resulting in the involuntary loss of urine. UI is common in women, but many of those affected do not mention symptoms to healthcare providers. The prevalence of the condition makes it likely that a large proportion of women attending for osteopathic care will be affected by symptoms of UI. It is not known whether osteopaths routinely ask about urinary UI, or provide advice. Aim: The primary aim of this research was to explore osteopaths' views and experiences regarding the identification of UI in women. Methods: This research was undertaken as an exploratory, qualitative study. A purposive sample of 11 osteopaths participated in semi-structured interviews. The data were analysed using a framework approach. Findings: A wide variation in views and experience of identifying and providing advice for urinary incontinence in women was found. Identification of UI occurred either by practitioners asking about symptoms; by following up on comments or observations; or, by patient led discussions. Conclusions: This study has identified barriers to discussing UI in routine osteopathic consultations. UI is common in women and those affected are often reluctant to seek help. Women can be helped to improve their symptoms if they are given appropriate advice. More awareness of the condition and appropriate advice may encourage more osteopaths to consider UI as part of routine care.